Effects of word length, contextual support, and prior second language proficiency on the learning of technical words in a second language - Jie Wang; Yen Na Yum (PLoS ONE, 2025)
Second language (L2) learners often struggle with learning technical words in a new discipline. Previous studies suggested that word length and context may differentially affect orthographic and semantic acquisition during initial L2 word learning. This study investigated how (1) target word length, (2) contextual support, and (3) learners’ L2 vocabulary and spelling abilities influence orthographic and semantic recognition in initial acquisition of L2 technical words. Eighty-eight Chinese-English university students read sentences with high- and low-constraint contexts about sixteen L2 English technical words and then performed orthographic and semantic recognition tasks. Recognition accuracy was examined through multiple-choice questions with fully and partially correct answer choices and analyzed with generalized linear mixed-effects models. Results showed that longer word length impaired orthographic recognition but facilitated partial semantic recognition, while contextual support enhanced semantic but not orthographic learning of L2 technical words. Skilled spellers performed better on orthographic recognition than poorer spellers, while those with larger L2 vocabulary size also showed better orthographic learning, especially for shorter word forms. Hence, word length, contextual support, and learners’ L2 vocabulary and spelling abilities differentially affected orthographic and semantic learning of L2 technical words, and measurement of partial recognition facilitated a nuanced understanding of learning outcomes. The findings highlight the importance of adopting targeted pedagogical approaches to enhance L2 technical word learning.